(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article provides conclusions and information on the methodology of foreign language teaching in Uzbekistan and its brief history, in particular, the analysis of practical scientific works in this field, the history of its development as a science, the types of modern methods used in the methodology of foreign language teaching. and it is about using them.